A Multi-modal HOTS-Oriented Worksheet Based on the PISA Reading Framework: Development and Validation Study in Middle School - Dewi, Lia Sylvia; Damaianti, Vismaia S.; Mulyati, Yeti; Nugroho, Rudi Adi (Edukasi, 2026)
This study developed and validated a digital multimodal student worksheet that integrates Higher-Order Thinking Skills (HOTS) and the PISA reading literacy framework for Indonesian middle school reading instruction. Although HOTS and literacy outcomes are emphasized in curriculum policy, teachers still have limited access to classroom-ready worksheets that systematically operationalize PISA cognitive processes (locating information, understanding, and evaluating/reflecting) within a single coherent learning tool. Addressing this gap, the study employed a Research and Development approach using the ADDIE model to design an LKPD that maps national competencies to PISA-oriented reading tasks supported by multimodal texts (e.g., infographics and charts). The product was reviewed by expert validators and piloted with seventh-grade students in a classroom setting. Validation results indicated that the LKPD met high standards of didactic, constructional, and technical quality and that the accompanying assessment items were appropriate for eliciting higher-order reading responses. The try-out data further showed that the LKPD can function diagnostically by revealing students’ recurring challenges in inferential comprehension and information integration, while also supporting engagement with evaluative and reflective prompts through multimodal task design. Overall, the findings suggest that the developed LKPD is a valid and feasible tool for implementing HOTS-oriented, PISA-aligned reading activities and for informing instructional decisions based on students’ domain-specific reading profiles. Future studies should examine broader implementation across diverse school contexts and evaluate learning impact over sustained use.